2016
DOI: 10.1177/1525822x16670625
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Time-limited Incentive on Participation by Hard-to-reach Respondents in a Panel Study

Abstract: We describe an experiment to provide a time-limited incentive among a random sample of 594 hard-to-reach respondents, 200 of whom were offered the incentive to complete all survey components of a study during a three-week winter holiday period. Sample members were primary caregivers of children included in the 2014 Child Development Supplement to the U.S. Panel Study of Income Dynamics. The incentive provided $50 to caregivers who completed a 75-minute telephone interview and whose eligible children each compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In addition, fieldwork progressed considerably faster, leading to higher response rates, a more effective use of the gross sample and thus greater cost-effectiveness. This is in line with findings on early bird incentives in other survey contexts (Brown & Calderwood, 2014; Carpenter & Burton, 2018; Fomby et al, 2017; Olsen, 2005). Furthermore, the positive impact of the early bird cash incentive on response rates was not limited to the panel registration phase but could still be observed over the course of the first year of panel survey waves.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, fieldwork progressed considerably faster, leading to higher response rates, a more effective use of the gross sample and thus greater cost-effectiveness. This is in line with findings on early bird incentives in other survey contexts (Brown & Calderwood, 2014; Carpenter & Burton, 2018; Fomby et al, 2017; Olsen, 2005). Furthermore, the positive impact of the early bird cash incentive on response rates was not limited to the panel registration phase but could still be observed over the course of the first year of panel survey waves.…”
Section: Discussionsupporting
confidence: 90%
“…So far, such early bird incentives have been primarily tested in surveys which use interviewers for all or some of the data collection (Fomby et al, 2017; LeClere et al, 2012). These studies have shown that early bird incentives increase response rates while at the same time reducing other types of fieldwork costs, such as repeated contact attempts by interviewers to sample units before an interview can be conducted (Brown & Calderwood, 2014; Olsen, 2005) or additional conversion attempts where interviewers follow up initially unsuccessfully recruited addresses (Carpenter & Burton, 2018).…”
Section: Background On Respondent Incentivesmentioning
confidence: 99%
“…The age-specific findings that we report must be interpreted in this context; that is, the experiment was more effective for older adults than younger adults without children. However, given the lack of differential effects of the incentives across a large number of sociodemographic characteristics demonstrated here and evidence regarding the utility of incentives in studies of families with children (e.g., Fomby et al 2015), there is reason to believe that similar effects would emerge for parents.…”
Section: Discussionmentioning
confidence: 79%
“…Likewise, results from the present study showed that receiving a personalized brief health assessment was associated with high PBC and high intention to participate in the NutriQuébec project. On the other hand, other studies have shown that providing a financial incentive was effective to encourage low-income, unemployed or hard-to-reach individuals to participate in a study [49][50][51]. Yu et al reported that the use of a modest monetary incentive ($10) in a longitudinal study increased the number of returned surveys [52].…”
Section: Discussionmentioning
confidence: 99%